Matrine suppresses cell growth of diffuse large B-cell lymphoma via inhibiting CaMKIIγ/c-Myc/CDK6 signaling pathway - Jianyou Gu; Xiao Wang; Ling Zhang; Jingjing Xiang; Jingya Li; Zheng Chen; Yu Zhang; Junfa Chen; Jianping Shen (BMC, 2021)
Abstract Background C-Myc aberrations confer a more aggressive clinic behavior in diffuse large B-cell lymphoma (DLBCL). Matrine is an alkaloid extracted from Sophora flavescens Ait. It possesses anti-cancer property through inhibiting the cell proliferation and inducing the apoptosis. The present study aimed to explore the underlying mechanisms of matrine in suppressing the cell growth of DLBCL. Methods The influence of matrine on the viability of cultured DLBCL cell lines SU-DHL-16 and OCI-LY3 cells were determined by CCK-8. Apoptosis and cell cycle were measured by flow cytometry after matrine exposure. Western blot was taken to investigate the expression of activated Caspase-3, cleaved PARP, c-Myc, phospho-c-Myc (Ser62), CaMKIIγ, phospho-CaMKIIγ (Thr287), CDK4 and CDK6 after matrine treatment. Cycloheximide chase analysis was used to determine the c-Myc protein half-lives before and after matrine treatment. Growth salvage analysis was taken by ectopic expression of c-Myc. Results In cultured DLBCL cells, matrine suppressed cell viability in a concentration and time dependent fashion. Matrine treated SU-DHL-16 and OCI-LY3 cells for 48 h with IC50 value of 1.76 mM and 4.1 mM, respectively. Matrine induced apoptosis through a caspase-independent pathway and caused G0/G1 cell cycle arrest in a concentration dependent manner in DLBCL cells. The protein expression of c-Myc was inhibited while the transcription of c-Myc was not reduced by matrine. c-Myc protein half-lives were decreased from 30.4, 69.4 min to 16.6, 15.9 min after matrine treatment in SU-DHL-16 and OCI-LY3, respectively. As a critical protein kinase of c-Myc, CaMKIIγ phosphorylation at Thr287 was found to be down-regulated and c-Myc phosphorylation at Ser62 was reduced together after matrine treatment in DLBCL. The growth suppression of SU-DHL-16 cells induced by matrine was rescued by over-expression of c-Myc achieved by recombinant adenovirus infection. The decreased expression of CDK6, not CDK4, induced by matrine was rescued by ectopic expression of c-Myc protein. Conclusions This study has shown for the first time that matrine suppresses cell growth of DLBCL via inhibiting CaMKIIγ/c-Myc/CDK6 signaling pathway.